2018
DOI: 10.1186/s13068-018-1025-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing methane production from lignocellulosic biomass by combined steam-explosion pretreatment and bioaugmentation with cellulolytic bacterium Caldicellulosiruptor bescii

Abstract: BackgroundBiogas production from lignocellulosic biomass is generally considered to be challenging due to the recalcitrant nature of this biomass. In this study, the recalcitrance of birch was reduced by applying steam-explosion (SE) pretreatment (210 °C and 10 min). Moreover, bioaugmentation with the cellulolytic bacterium Caldicellulosiruptor bescii was applied to possibly enhance the methane production from steam-exploded birch in an anaerobic digestion (AD) process under thermophilic conditions (62 °C).Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 68 publications
3
25
1
1
Order By: Relevance
“…Total gas production and CH 4 production from TRT were both higher than that from CON, but the increases were both statistically insignificant. The results are not consistent from previous studies ( Lizasoain et al, 2017 ; Mulat et al, 2018 ), which reported that steam explosion pretreatment significantly increased the total gas production and CH 4 production. Steam explosion pretreatment improved the digestibility of corn stover and more readily fermentable substrates should produce more gas.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Total gas production and CH 4 production from TRT were both higher than that from CON, but the increases were both statistically insignificant. The results are not consistent from previous studies ( Lizasoain et al, 2017 ; Mulat et al, 2018 ), which reported that steam explosion pretreatment significantly increased the total gas production and CH 4 production. Steam explosion pretreatment improved the digestibility of corn stover and more readily fermentable substrates should produce more gas.…”
Section: Resultscontrasting
confidence: 99%
“…In addition, the anaerobic digestion inoculum used in the present study is rumen fluid, which is home to a vast array of ciliate protozoa, fungi, bacteria, and archaea. The compositions and interactions of different microbes are more complex than those used in the previous studies ( Lizasoain et al, 2017 ; Mulat et al, 2018 ). In the present study, the formation of propionate might be served as an alternative to H 2 formation and then reduce the utilization of H 2 in methanogenesis, shifting H 2 flow from CH 4 to propionate production.…”
Section: Resultsmentioning
confidence: 94%
“…Caldicoprobacter has also been found to be enriched in anaerobic digesters fed lignocellulosic biomass under both mesophilic and thermophilic conditions [53,54]. Moreover, it has been shown to dominate in an anaerobic digester with high total ammonium-nitrogen (5 to 25 g/L) and, as in this study, high VFA levels (>4 g/L) [55].…”
Section: Phylogenetic Analysissupporting
confidence: 65%
“…The intricate composition of lignocellulosic materials, where cellulose fiber is tightly linked to hemicellulose and lignin, hinders their biodegradability and thus limits their use as co-substrates for AD. The recalcitrant nature of the LW necessitates the inclusion of the pretreatment step (physical, chemical or biological) for their efficient conversion into biofuels [34]. The use of thermophilic digesters can eliminate the use of costly and sometimes hazardous pretreatment steps.…”
Section: Introductionmentioning
confidence: 99%